1984
DOI: 10.1007/bf01451519
|View full text |Cite
|
Sign up to set email alerts
|

CPS 758 Untersuchung des Mischungsgleichgewichts bin�rer Polymermischungen

Abstract: The phase diagram of a binary polymer blend can be derived from the glass temperatures Tg of the demixed phases under the following conditions:1. The Tg's of the pure components are sufficiently different from one another. 2. The Tg's of the one-phase homogeneous mixtures can be determined and vary monotonically with composition.3. The equilibrium state of the mixture is attained after sufficient long annealing at temperature T.4. The equilibrium state at the temperature T can be frozen by quenching. These con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

1987
1987
1999
1999

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…In addition, this blend displayed single-Tg behavior (cf. conclusions regarding miscibility of PS/TMPC blends, as summarized in Tables I and II, compare favorably with the phase diagrams reported by Illers et al [9]. The present DSC results for the PS/TMPC binary blends indicate that, for out purposes, the observation of a single glass transition with Tg well-predicted by Equation (2) serves well as the criterion for phase homogeneity.…”
Section: Ps/tmpc Binary Blendssupporting
confidence: 88%
See 3 more Smart Citations
“…In addition, this blend displayed single-Tg behavior (cf. conclusions regarding miscibility of PS/TMPC blends, as summarized in Tables I and II, compare favorably with the phase diagrams reported by Illers et al [9]. The present DSC results for the PS/TMPC binary blends indicate that, for out purposes, the observation of a single glass transition with Tg well-predicted by Equation (2) serves well as the criterion for phase homogeneity.…”
Section: Ps/tmpc Binary Blendssupporting
confidence: 88%
“…Published studies [6][7][8] on PS/TMPC blends have shown that this pair is miscible at lower temperatures but exhibits a lower critical solution temperature (LCST) in the vicinity of 230 °C. More recently, Illers et al [9] reported phase diagrams of PS/TMPC blends in which the molecular weight of PS was systematically varied; the phase separation process was shown to be reversible, in support of the thermodynamic miscibility at lower temperatures. As for the TMPC/PPO pair, previous DSC and density measurements I I{}] indicated clear immiscibility in the accessible temperature range.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…where ri is obtained from (7) In the above relation, T f , P," , and p' are the equation of state parameters and Mi is the molecular weight of species i. The total mixing interaction energy 8 ; was also given as where el2 is the nonspecific mer-mer interaction between mer 1 and mer 2 and the additional energy attributed to the specific interaction fspecific was obtained…”
Section: The Generalized Lattice-fluid Model By Sanchez and Balazs'mentioning
confidence: 99%